An Outcome-based Muay Thai Training Program - Napong Romkaew; Canthasap Chompoopat; Therdsak Supandee (Gemilang Maju Publikasi Ilmiah (GMPI), 2025)
This research mainly aimed to construct an outcome-based Muay Thai training program which employed the needs of stakeholders for developing a Muay Thai training program and the results of a meta-analysis as factors that could be acted on. The needs and the results were integrated with concepts, theories, and components of common Muay Thai trainings to develop an outcome-based Muay Thai training program. More data sources for developing the Muay Thai training program included 1) an evaluation of the Muay Thai training program by means of program critique in a focus group discussion among seven experts, and 2) an evaluation of quality control standards through a five-rating-scale evaluation form. This evaluation covered the following espects of the quality control standards of the outcome-based Muay Thai training program; Accuracy Standards, Propriety Standards, Feasibility Standards, and Utility Standards. The research results showed the means of the quality control standards as follows; Accuracy Standards (4.40), Propriety Standards (4.36), Feasibility Standards (4.24), and Utility Standards (4.40). The overall evaluation result of the constructed Muay Thai training program had an average of 94.60 percent.